Association of Breastfeeding and Child IQ Score at Age 5 Years. Issue 4 (April 2021) - Plunkett, Beth A.; Mele, Lisa; Casey, Brian M.; Varner, Michael W.; Sorokin, Yoram; Reddy, Uma M.; Wapner, Ronald J.; Thorp, John M.; Saade, George R.; Tita, Alan T.N.; Rouse, Dwight J.; Sibai, Baha; et al.
Abstract : OBJECTIVE: To evaluate whether breastfeeding and its duration are associated with a reduced risk of low IQ scores or other neurodevelopmental problems. METHODS: We conducted a secondary analysis of two parallel multicenter, double-blinded randomized controlled trials in which participants with a singleton pregnancy and either subclinical hypothyroidism or hypothyroxinemia were treated with thyroxine or placebo. Our primary outcome was a low IQ score (less than 85 on the WPPSI-III [Wechsler Preschool and Primary Scale of Intelligence III] at age 5 years). Secondary outcomes included performance measures on other validated neurodevelopmental tests. Univariable and multivariable analyses were performed to evaluate the association between breastfeeding and neurodevelopmental outcomes. Stepwise backward proceeding linear and logistic regression models were used to develop the final adjusted models. RESULTS: Of the 772 participants studied, 614 (80%) reported breastfeeding. Of these, 31% reported breastfeeding for less than 4 months, 19% for 4–6 months, 11% for 7–9 months, 15% for 10–12 months and 23% for more than 12 months. IQ scores were available for 756 children; mean age-5 scores were higher with any breastfeeding (96.7±15.1) than without (91.2±15.0, mean difference 5.5, 95% CI 2.8–8.2), and low IQ scores were less frequent with any breastfeeding (21.5%) than with no breastfeeding (36.2%, odds ratio 0.48, 95% CI 0.33–0.71). In adjusted analyses, breastfeeding remained associated with reduced odds of low IQ score (adjusted odds ratio [aOR] 0.62, 95% CI 0.41–0.93), and each additional month of breastfeeding was associated with lower odds of a low IQ scores (aOR 0.97, 95% CI 0.939–0.996). No significant associations between breastfeeding and other neurodevelopmental outcomes were identified in adjusted analyses. CONCLUSION: Breastfeeding and its duration are associated with lower odds of low IQ score at age 5 years. Abstract : Breastfeeding and its duration are associated with a lower risk of a low IQ score (less than 85) at age 5 years.